INTEGRATED TOPOLOGY OPTIMIZATION OF STRUCTURE /CONTROL FOR PIEZOELECTRIC SMART PLATE AND ITS TOPOLOGY EXTRACTION BASED ON MICRO-GENETIC ALGORITHM - HE JianJun; CHEN XiangZi (Jixie qiangdu)
The integrated topology optimization design with respect to the structural topology configuration,the placements and the numbers of actuators as well as the control system weight parameters of a cantilever piezoelectric intelligent plate is studied in this paper,. The simultaneous optimization and topology extraction are realized by combining with design of linear quadratic optimal control system in coupled modal space,and strategies based on micro-genetic algorithm and wavelet analysis for noise reduction. Results of numerical examples show that the presented new method is rational and effective,with small computational cost and high efficiency. Meanwhile,clear structural topology and high control performances are obtained.